Synovial cell sarcoma in a dog: A misnomer—Cytologic and histologic findings and review of the literature. (6th February 2018) - Monti, Paola; Barnes, Darren; Adrian, Anna M.; Rasotto, Roberta
Abstract: A 4‐year‐old Irish Setter was presented with a history of progressive left pelvic limb lameness. Orthopedic examination revealed pain on manipulation of the left stifle. Radiographs showed an osteolytic lesion in the subchondral bone of the medial tibial condyle. Fine‐needle aspirates were taken, and cytology revealed numerous cohesive clusters of plump, oval to spindloid cells often with perivascular distribution and moderate cellular atypia. A diagnosis of sarcoma was made with synovial cell sarcoma (SCS) and histiocytic sarcoma being the 2 main differentials. Histopathology confirmed the diagnosis of sarcoma and provided the same differentials. All neoplastic cells were positive for vimentin, and approximately 5% of them also stained with pan‐cytokeratin using immunohistochemical staining methods. Neoplastic cells did not express CD18. The combination of this immunohistochemical profile and cell morphology was consistent with an SCS. Synovial cell sarcoma is a rare and poorly understood canine tumor entity. This is the first extensive description of the cytologic features of this neoplasm. The literature was also reviewed, focusing on comparative aspects of dogs and people, with a special emphasis on the cell of origin and diagnostic tools. Controversies regarding the nomenclature of this tumor are also presented. The authors propose a new term (cytokeratin‐positive joint‐associated sarcoma) for addressing this neoplasm until the cell of origin of this tumor is elucidated.